Progress in quality of life assessment of breast cancer. The measurement system of EORTC - Illarramendi, José Juan; Manterola, Ana; Salgado, Esteban; Domínguez, Miguel Ángel; Arraras, Juan Ignacio (Psicooncología, 2007)
The aim of the present work is to present the situation of Quality of Life assessment in breast cancer. Breast cancer is the tumour site in which more Quality of Life studies have been carried out. Quality of Life assessment can be quite useful in clinical practice, clinical trials and in the patients’ adaptation process to their situation, including decision making. The EORTC assessment system for breast cancer and two other instruments are presented. Special attention is paid to the Quality of Life assessment areas in which we consider that more progress is being performed nowadays: the sentinel node biopsy, the different surgery modalities, the experience of elderly patients, the differences among age based groups, and the long term follow-up studies.
Keywords: Quality of life; Measurement; Breast cancer; Eortc